Occulted - Rose, Amy, 1987-; Estrada, Ryan, 1980- (Iron Circus Comics, 2023)
Survivor Amy Rose recounts her upbringing in an abusive cult which forbade independent learning, and how she discovered books in a secret library that opened up her world and inspired her to escape.--Publisher.